Which neurological diseases are most likely to be associated with "symptoms unexplained by organic disease" - Stone, J; Carson, A; Duncan, R; Roberts, R; Coleman, R; Warlow, C; Murray, G; Pelosi, A; Cavanagh, J; Matthews, K; Goldbeck, R; Sharpe, M (2012)
Many patients with a diagnosis of neurological disease, such as multiple sclerosis, have symptoms or disability that is considered to be in excess of what would be expected from that disease. We aimed to describe the overall and relative frequency of symptoms 'unexplained by organic disease' in patients attending general neurology clinics with a range of neurological disease diagnoses. Newly referred outpatients attending neurology clinics in all the NHS neurological centres in Scotland, UK were recruited over a period of 15 months. The assessing neurologists recorded their initial neurological diagnoses and also the degree to which they considered the patient's symptoms to be explained by organic disease. Patients completed self report scales for both physical and psychological symptoms. The frequency of symptoms unexplained by organic disease was determined for each category of neurological disease diagnoses. 3,781 patients participated (91% of those eligible). 2,467 patients had a diagnosis of a neurological disease (excluding headache disorders). 293 patients (12%) of these patients were rated as having symptoms only ''somewhat'' or ''not at all'' explained by that disease. These patients self-reported more physical and more psychological symptoms than those with more explained symptoms. No category of neurological disease was more likely than the others to be associated with such symptoms although patients with epilepsy had fewer. A substantial proportion of new outpatients with diagnoses of neurological disease also have symptoms regarded by the assessing neurologist as being unexplained by that disease; no single neurological disease category was more likely than others to be associated with this phenomenon. © Springer-Verlag 2011.